Artificial satellites dynamics: Resonant effects - Sampaio, Jarbas Cordeiro [UNESP] (2012)
In this work, the resonance problem in the artificial satellites motion is studied. The development of the geopotential includes the zonal harmonics J20 and J40 and the tesseral harmonics J22 and J42. Through successive Mathieu transformations, the order of dynamical system is reduced and the final system is solved by numerical integration. In the simplified dynamical model, two critical angles are studied, 2201 and 4211. Numerical results show the time behavior of the semi-major axis and 2 angle.